Prolactin does not seem to mediate the improvement on insulin resistance markers and blood glucose levels related to breastfeeding - Oliveira, Julia Martins de; Dualib, Patricia Medici; Ferraro, Alexandre Archanjo; Carvalho, Camila Rodrigues de Souza; Mattar, Rosiane; Dib, Sérgio Atala; Almeida-Pititto, Bianca de (Frontiers in Endocrinology, 2023)
Introduction: The prevalence of type 2 diabetes mellitus (T2DM) is increasing worldwide. Strategies to decrease this risk should be strongly encouraged. Lactation has been associated, for the mother, with reduction in future T2DM risk in several studies. The mechanisms behind this phenomenon, however, are poorly understood. The aims of this study were, first, to compare blood glucose levels and MIR in early postpartum women with overweight/obesity according to their breastfeeding status and, second, to evaluate whether prolactin (PRL) levels could mediate improvements in these parameters. Methods: The prospective study followed 95 women older than 18 years from early pregnancy for up to 60 to 180 days postpartum. All participants had a BMI > 25 kg/m2 and a singleton pregnancy. At each visit, questionnaires, clinical and biochemical evaluations were performed. Participants were divided into two groups according to the breastfeeding status as "yes" for exclusive or predominant breastfeeding, "no" for not breastfeeding. Results:Breastfeeding women (n=44) had significantly higher PRL levels [47.8(29.6-88.2) vs. 20.0(12.0-33.8), p<0.001].They also had significantly lower fasting blood glucose levels [89.